MEASURING THE RELATIONSHIP BETWEEN GOVERNMENT SPENDING AND ECONOMIC GROWTH - Adnan Kareem farhad (Scholar Express Journal, 2023)
In this study, the focus is on investigating the relationship between government spending and economic growth in Iraq. By analyzing data from multiple sources spanning a period of 10 years (2010-2020), the impact of government spending on the economy is evaluated. The findings of this research reveal that government spending does have a positive effect on economic growth in Iraq, although the magnitude of this impact varies across different sectors. This study can be beneficial for policymakers as it can assist them in creating policies that promote sustainable economic development in Iraq
Keywords: different; policymakers; effect; beneficial